ANALISIS ETIKA SITUASI JOSEPH FLETCHER PADA KONSEP PAÑCA NṚTA (LIMA JENIS KEBOHONGAN YANG DIPERBOLEHKAN) DALAM SUSASTRA HINDU - Gede Agus Siswadi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The word lying is known as a bad word, it should not be done, it is forbidden by religion, and it is a sin to commit an act of lying. This statement is true if lying is done with the aim of deceiving or fooling someone. However, it is different from the act of lying which is done to achieve happiness, and with a noble purpose, or when a difficult situation causes the lie to be done. So lying is justified. As in the concept of pañca nṛta or five types of lies that are justified in Hindu religious teachings. This study uses a philosophical hermeneutic method with the analysis pattern of Miles and Huberman. The results of this study are 1). Situation ethics from Joseph Fletcher explains that actions are said to be good if they are based on love, and in the right situation. Good deeds will become evil if done without love or not in the right situation, and vice versa. Bad deeds will become good when done with love and the right circumstances. 2). The concept of pañca nṛta is the five types of lies that are justified, these must be related to the right situation and based on love. 3). The concept of pañca nṛta, if it is done with a good purpose, it will produce something good, but if it is done with a bad purpose, it will receive karma or sin.